NH2-MOF-coated SiO2 core-shell type nano composite particle electrorheological fluid and preparation method thereof

By synthesizing anisotropic amino-modified MOF nanoparticles by hydrothermal method in the current transforming liquid, and coating silica with hydrolysis to form core-shell nanocomposite particles, the existing current transforming liquid under high electric field conditions is solved. The problem of insufficient shear stress changes and insufficient anti-settlement performance has been achieved, which significantly improves the current transformation efficiency and anti-settlement ability.

CN119391470APending Publication Date: 2025-02-07QINGDAO UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411467408.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The shear stress changes of existing current-change liquids under high electric field conditions and their anti-settlement performance is insufficient, which affects its current-change performance.

Method used

The hydrothermal method is used to synthesize round cake anisotropic amino-modified MOF nanoparticles, and the silica is coated through hydrolysis to form core-shell nanocomposite particles, and combined with dimethyl silicone oil to form an electrostatic liquid.

Benefits of technology

The current transformation efficiency and anti-settlement ability of the current transformation liquid are significantly improved, and its shear stress response ability under high electric field conditions is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119391470A_ABST
    Figure CN119391470A_ABST
Patent Text Reader

Abstract

The invention relates to an NH2-MOF coated SiO2 core-shell type nano composite particle electrorheological fluid and a preparation method thereof. A dispersion phase of the electrorheological fluid is a nano composite particle composed of round cake type anisotropic amino modified MOF and silicon dioxide nano particles coated on the round cake type anisotropic amino modified MOF, and a continuous phase of the electrorheological fluid is dimethyl silicone oil; the preparation process comprises the following steps: firstly, preparing cake-shaped NH2-MOF nano-particles by adopting a hydrothermal method, and then coating silicon dioxide on the cake-shaped NH2-MOF nano-particles by adopting a hydrolysis method, so as to finally prepare the anisotropic NH2-MOF coated SiO2 nano-composite material. The size diameter of the anisotropic NH2-MOF coated SiO2 nano composite particles is 250-350nm, the anti-settling performance of the electrorheological fluid is enhanced by utilizing the porous structure, high porosity and the like of MOF, the asymmetry of a crystal structure is increased by introducing a polar group to improve the polarization capability, and the overall performance of the material is remarkably enhanced by the comprehensive improvement. And particularly, the electrorheological property is outstanding. The drawing shows a relational graph of the shear strength and the shear rate of the NH2-MOF coated SiO2 core-shell type nano composite particle electrorheological fluid.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an electrorheological fluid material and a preparation method thereof, and in particular to an NH2-MOF@SiO2 nanocomposite particle electrorheological fluid material and a preparation method thereof. Background Art

[0002] The research history of electrorheological fluid (ERF) can be traced back to 1947, when Willis Winslow of the United States pioneered the mixing of dispersed particles and base fluid to form a suspension system. As an advanced intelligent suspension, electrorheological fluid is a mixture of electropolarized particles and insulating oil in a certain proportion. Under the action of an external electric field, micro-nanoparticles will react within a response time of 0.01 seconds to generate columnar chain aggregation, which leads to anti-shear stress in the direction perpendicular to the electric field, and reversibly transform from a Newtonian fluid with good fluidity and shear-independent viscosity (shear stress increases linearly with shear rate, and shear viscosity is almost a constant value.) to a solid-like viscoelastic body with non-vanishing yield stress, enhanced shear viscosity and dynamic modulus (shear stress remains stable in the low shear rate region, but as the rate continues to increase, the stress will also increase.) When the voltage is removed, its rheological properties will be restored, which has a reversible effect on its shear stress and viscosity.

[0003] In recent years, metal-organic framework (MOFs) materials have attracted widespread attention as an emerging research trend. This type of material belongs to an organic-inorganic composite hybrid system. The core feature is that it is connected to organic ligands through a self-assembly mechanism with metal ions as the central node. MOF is generally highly crystalline and can be self-assembled under experimental conditions such as hydrothermal. It also has unique structural characteristics such as high porosity and large specific surface area. Its structure is diverse and can be designed. Its surface is porous. Given the good modifiability of these pore surfaces and the reversibility of coordination bonds, we can flexibly access a variety of functional groups on organic ligands, such as amino (-NH2) and bromine (-Br). By cleverly introducing polar groups such as amino groups, the asymmetry of the crystal structure can be increased, the polarization response speed of the system can be improved, and the improvement of polarization ability can enhance the electrorheological properties. It can give full play to the excellent anti-sedimentation performance of MOF, refine the particle size on the original basis, increase the surface and interface area, and improve the dielectric properties of the system.

[0004] Object and content of the invention

[0005] The purpose of the present invention is to provide an NH2-MOF@SiO2 core-shell nanocomposite particle electrorheological fluid material, wherein the nanocomposite particles composed of disc-shaped anisotropic amino-modified MOF and silica nanoparticles coated thereon serve as the dispersed phase; dimethyl silicone oil is the continuous phase.

[0006] The present invention also aims to provide a method for preparing NH2-MOF@SiO2 core-shell nanocomposite materials, which mainly improves polarization and electrorheological properties by first introducing amino groups when synthesizing MOF, and then further improves electrorheological properties by controlling the amount of silicon dioxide to regulate the thickness of the coating layer. The preparation process of the obtained core-shell nanocomposite materials includes a hydrothermal method and a hydrolysis method. The preparation process is to first prepare round cake-shaped NH2-MOF nanoparticles by a hydrothermal method, and then coat silicon dioxide thereon by a hydrolysis method, and finally prepare anisotropic NH2-MOF@SiO2 core-shell nanocomposite materials. The anisotropic NH2-MOF@SiO2 nanocomposite materials combine dual advantages: anisotropy and core-shell type, and have multiple advantages such as small size of nanoparticles. The introduction of polar groups increases the asymmetry of the crystal structure to improve the polarization ability, and the surface of the amino-modified MOF is coated with chemically stable and highly insulating silicon dioxide to adjust the conductivity. In short, this comprehensive improvement significantly enhances the overall performance of the material, especially in terms of electrorheological properties.

[0007] The purpose of the present invention can be achieved through the following technical scheme: the electrorheological fluid (ERF) prepared by the present invention, the nanocomposite particles composed of the disc-shaped anisotropic amino-modified MOF and the silica nanoparticles coated thereon are used as the dispersed phase; dimethyl silicone oil is the continuous phase.

[0008] The above-mentioned NH2-MOF is prepared by a hydrothermal method, and the preparation process is as follows:

[0009] (1) Add 65 mL of N,N-dimethylformamide (DMF) and 10 mL of anhydrous methanol to a beaker in sequence. Stir well and weigh 2.8 g of aminoterephthalic acid (NH2-TPA) and 0.7 g of terephthalic acid (TPA) into the solution. Then weigh 0.7 g of hexadecyltrimethylammonium bromide (CTAB) and slowly add it to the prepared mixed solution. Stir at room temperature until all the solution is observed to be dissolved.

[0010] (2) 3.5 ml of acetic acid was slowly injected into the above solution, followed by thorough stirring for 10 minutes. Next, 2 ml of tetrabutyl titanate (TBT) was added dropwise to the continuously stirred mixture, and stirring was continued for 20 minutes. After thorough mixing, the mixture was transferred to a reactor and the temperature was set at 150 degrees Celsius for a 24-hour hydrothermal reaction process.

[0011] (3) The suspension generated after the reaction was first washed once with dimethylformamide at a speed of 7500 r / min, then washed twice with anhydrous methanol and three times with anhydrous ethanol to remove internal impurities, and the product was dried at 75°C for 10 hours.

[0012] NH2-MOF@SiO2 core-shell nanocomposite materials and their electrorheological fluids were prepared by the following method:

[0013] (1) Measure 150 mL of anhydrous ethanol and put it into a 200 mL beaker for later use. Weigh 0.5 g of NH2-MOF nanoparticles and dissolve them in it. Stir for 20 min.

[0014] (2) Measure and mix 1.2 mL of deionized water and 1 mL of ammonia water to form a mixed solution, and stir for 15 min. Then add 2 mL of tetraethyl orthosilicate (TEOS) and stir for 4 h to form a suspension.

[0015] (3) After the hydrolysis reaction, the suspension was washed by centrifugation three times with anhydrous ethanol, transferred to a drying oven, and dried at 75°C for 12 h to obtain a solid powder.

[0016] (4) The obtained solid powder and dimethyl silicone oil are prepared into an electrorheological fluid at a weight ratio of 10 wt %.

[0017] Compared with the prior art, the present invention has the following significant advantages:

[0018] 1. The preparation method of the present invention involves a hydrothermal method and a hydrolysis method, and NH2-MOF@SiO2 core-shell nanocomposite particles are prepared in two steps. The preparation process is simple and has no special requirements for experimental instruments. The sample is in the shape of a round cake and has a regular spatial structure.

[0019] 2. On this basis, the electrorheological fluid formed by mixing the material with dimethyl silicone oil has a better electrorheological efficiency. Its nano-scale size makes the sample have a larger specific surface area and a smaller particle density, which greatly improves the material's anti-sedimentation ability.

[0020] 3. The introduction of amino polar groups increases the asymmetry of the crystal structure and improves the polarization response speed of the system. At the same time, combined with the advantages of porous anisotropic structures, the dielectric properties are improved, so that the nanoparticles have a fast electric field response speed; the amino-modified MOF is coated with chemically stable and highly insulating silica to form a core-shell structure, which improves the conductive properties, gives full play to the unique advantages of composite materials, and shows excellent electrorheological properties. The entire reaction process is not only easy to operate, but also environmentally friendly, non-toxic and harmless throughout the process, and has low requirements for production equipment. Its preparation process is efficient and simple, raw materials are easy to obtain, and the composition and performance can be flexibly regulated, which promotes its feasibility in industrial production and expands its wide application in many fields. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 SEM image of the obtained NH2-MOF of 4NH2-TPA:TPA

[0022] Figure 2 XRD pattern of the obtained NH2-MOF of 4NH2-TPA:TPA

[0023] Figure 3 Transmission electron microscopy image of the obtained 4NH2-TPA:TPA NH2-MOF

[0024] Figure 4 The relationship between the shear strength and shear rate of the electrorheological fluid made of NH2-MOF nanoparticles of 4NH2-TPA:TPA

[0025] Figure 5 SEM image of NH2-MOF@SiO2 nanoparticles of 4NH2-TPA:TPA prepared by coating with 2mLTEOS

[0026] Figure 6 Transmission electron microscopy image of NH2-MOF@SiO2 core-shell nanocomposite of 4NH2-TPA:TPA prepared by coating with 2mLTEOS

[0027] Figure 7 XRD pattern of NH2-MOF@SiO2 core-shell nanocomposite of 4NH2-TPA:TPA prepared by coating with 2mLTEOS

[0028] Figure 8 The relationship between shear strength and shear rate of the electrorheological fluid made of NH2-MOF@SiO2 composite particles of 4NH2-TPA:TPA prepared by coating with 2mLTEOS

[0029] Fig. 9 Transmission electron microscopy image of 4NH2-MOF@SiO2 core-shell nanocomposite prepared by coating with 1.25mLTEOS

[0030] Fig.10 The relationship between shear strength and shear rate of the electrorheological fluid made of 4NH2-TPA:TPA NH2-MOF@SiO2 composite particles prepared by coating with 1.25mLTEOS

[0031] Fig.11 Scanning electron microscope image of NH2-MOF@SiO2 nanoparticles of 4NH2-TPA:TPA prepared after coating with 1mLTEOS

[0032] Fig.12 XRD pattern of NH2-MOF@SiO2 core-shell nanocomposite of 4NH2-TPA:TPA prepared by coating with 1mLTEOS

[0033] Fig.13 The relationship between shear strength and shear rate of the electrorheological fluid made of 4NH2-TPA:TPA NH2-MOF@SiO2 composite particles prepared by coating with 1mLTEOS

[0034] Fig.14 XRD pattern of SiO2 DETAILED DESCRIPTION

[0035] Example 1 (Preparation of NH2-MOF (NH2-MOF①) nanoparticles of 4NH2-TPA:TPA):

[0036] 65mL of DMF and 10mL of anhydrous methanol were added to the beaker in turn. After stirring evenly, 2.8g of NH2-TPA and 0.7g of TPA were weighed and put into the solution. Then 0.7g of surfactant CTAB was weighed and added to the mixed solution. Stir at room temperature until all dissolved. After that, 3.5mL of acetic acid was added dropwise to the above solution and stirred for 10 minutes. After ensuring uniformity, 2mL of TBT was added. After continuous stirring for 20 minutes, the mixture was transferred to the reactor and subjected to hydrothermal reaction at 150°C for 24 hours. After natural cooling, the obtained suspension was first washed once with DMF at a speed of 7500r / min, and then washed twice with anhydrous methanol and three times with anhydrous ethanol to remove internal impurities. Finally, the product was dried at 75°C for 10 hours to obtain NH2-MOF① nanoparticles. The scanning electron microscope image of the obtained nanoparticles is shown as follows: Figure 1 As shown, the particles are round (square edge), the surface of the particles is not smooth, the morphology is uniform, and the particle diameter is about 270nm; the transmission electron microscope picture is as follows Figure 3 As shown in the figure, it can be observed that there are many holes corroded by titanic acid inside the particles, and there are defects inside the particles, which increases the specific surface area. Figure 2 As shown, the XRD pattern of the sample is the same as that of pure MIL-125. The diffraction peak intensity is obvious, with obvious sharp angles and good crystallinity. Take 0.15g of NH2-MOF sample and place it in 1.5mL silicone oil and grind it evenly at room temperature. Mix and prepare an electrorheological fluid (weight ratio is 10%), and use an electrorheometer to measure its electrorheological properties under different external electric field conditions, and obtain the relationship between shear stress and shear rate, as shown in the figure. Figure 4 Generally, the electrorheological efficiency can be used to reflect the strength of the electrorheological effect of electrorheological fluids with the same mass ratio. The calculation formula is generally: λ = (τ E -τ 。 ) / τ 。 Under the conditions of Example 1, when the voltage is set to 3 kV, the shear rate specific value of 0.1 s is selected. -1When the electrorheological efficiency of the sample is 273, it can be observed that it has a certain electrorheological effect, but under high voltage, its shear stress does not change with voltage.

[0037] Example 2 (preparation of NH2-MOF①@SiO2 core-shell nanocomposite particles and electrorheological fluid prepared by coating with 2mLTEOS):

[0038] Measure 150mL of anhydrous ethanol and put it into a 200mL beaker for use. Weigh 0.5g of NH2-MOF① nanoparticles, dissolve it in it, and stir for 20 minutes. Measure and mix 1.2mL of deionized water and 1mL of ammonia water to form a mixed solution, and stir for 15 minutes. Then add 2mL of LTEOS and stir at a constant speed for 4 hours to form a suspension. Wash it three times by centrifugation with anhydrous ethanol, transfer it to a drying oven, and dry it at 75°C for 12 hours to obtain a solid powder. The scanning electron microscopy of the prepared sample is as follows Figure 5 , transmission electron microscopy Figure 6 , the observation results show that the sample presents a regular morphology, specifically, the round cake-shaped particles with a diameter between 250 and 350nm are basically a little larger than the size of the amino MOF before coating, which indirectly confirms that some particles are successfully coated. Under the clear field of view of the transmission electron microscope, it can be identified that there are holes inside the particles, but the number of these holes is reduced compared to the template. This finding proves that the silica coating process successfully filled some of the holes. In addition, the particles show excellent monodispersity, ensuring their uniformity. Further analysis of the image shows that the SiO2 coating layer is observed, with a thickness of about 25nm. The XRD spectrum of this sample is Figure 7 , the diffraction peak is obvious. Compared with pure NH2-MOF①, it can be found that the intensity of its diffraction peak decreases. The XRD diagram of silicon dioxide is Fig.14 , proving that the coating of amorphous non-crystalline silicon dioxide makes the diffraction peak intensity of NH2-MOF①@SiO2 core-shell nanocomposite material decrease compared with the template. Subsequently, using precise electrorheological performance testing equipment, the ER effect of the sample was systematically tested under various external electric fields, and the relationship between shear stress and shear rate (ER curve) was obtained, such as Figure 8As shown. When observed under the condition of no electric field, we found that the shear stress showed a linear and gradually increasing trend with the increase of shear rate. This characteristic significantly demonstrated its typical behavior as a Newtonian fluid. When the electric field acts on the system, the change pattern of the shear stress changes and the increase of the shear stress becomes more significant with the increase of the shear rate, highlighting the characteristics of the Bingham fluid. This phenomenon proves that different electric field strengths will regulate the shear stress of the electrorheological fluid, showing that the coating and amino modification of silica greatly improve the electrorheological properties. The ER curve has a platform area, and its shear stress platform area is also close to 360Pa at 3000 volts. Under the conditions of Example 2, when the voltage is set to 3 kilovolts, the specific value of the shear rate of 0.1s is selected. -1 When the electrorheological efficiency of the obtained sample is 579, it is significantly higher than that before coating. Under high electric field conditions, the shear stress changes more significantly with the electric field. The sample has excellent electrorheological properties.

[0039] Example 3 (preparation of NH2-MOF①@SiO2 core-shell nanocomposite particles and electrorheological fluid prepared by coating with 1.25m LTEOS):

[0040] Measure 150mL of anhydrous ethanol and put it into a 200mL beaker for standby use. Weigh 0.5g of NH2-MOF① nanoparticles, dissolve it in it, and stir for 20 minutes. Measure and mix 1.2mL of deionized water and 1mL of ammonia water to form a mixed solution, and stir for 15 minutes. Then add 1.25mL of LTEOS, stir at a constant speed for 4 hours to form a suspension, wash it three times by centrifugation with anhydrous ethanol, transfer it to a drying oven, and dry it at 75°C for 12 hours to obtain a solid powder. The transmission electron microscopy image of NH2-MOF@SiO2 nanocomposite particles prepared by hydrolysis is shown in the figure. Fig. 9 As shown in the figure, the sample is a regular round cake-shaped particle of about 280 nanometers. It is clearly seen from the transmission electron microscope that there are holes inside the particles, but they are less than the template. The composite particles with a dosage of more than 2mL have good monodispersity, proving that the silica coating fills some of the holes and the dosage is insufficient to fill all the holes. Its ER curve is shown in Fig.10 It can be observed that with the increase of electric field, the shear stress increases significantly, and has a characteristic platform area of ​​ER curve. At 2 kV, the shear stress in this area can reach 157 Pa, but the sample only measured 2 kV. Overall, it also has good electrorheological properties, but still needs further optimization.

[0041] Example 4 (preparation of NH2-MOF①@SiO2 core-shell nanocomposite particles and electrorheological fluid prepared by coating with 1 ml LTEOS):

[0042] Measure 150mL of anhydrous ethanol and put it into a 200mL beaker for use. Weigh 0.5g of NH2-MOF① nanoparticles, dissolve it in it, and stir for 20 minutes. Measure and mix 1.2mL of deionized water and 1mL of ammonia water to form a mixed solution, and stir for 15 minutes. Then add 1mL of LTEOS and stir at a constant speed for 4 hours to form a suspension. Wash it three times by centrifugation with anhydrous ethanol, transfer it to a drying oven, and dry it at 75°C for 12 hours to obtain a solid powder. The scanning electron microscope image of the prepared sample is as follows: Fig.11 , it can be seen that the sample is a regular round cake-shaped particle with uniform size, but the particles are seriously adhered to each other, which is caused by the coating of silica. The XRD spectrum of the sample is as follows Fig.12 , the diffraction peak is obvious, and Figure 7 The diffraction peak intensity is reduced. Subsequently, the electrorheological effect of the sample obtained in Example 4 under various external electric fields was systematically tested using a precise electrorheological performance testing device. The ER curve is shown in FIG. Fig.13 Under the conditions of Example 4, when the voltage is set to 3 kV, the shear rate specific value of 0.1 s is selected. -1 When the electrorheological efficiency of the obtained sample is 487, the ER performance is significantly improved compared with that before coating. The coating and amino modification of silica greatly improve the electrorheological properties.

Claims

1. A NH2-MOF@SiO2 core-shell nanocomposite particle electrorheological fluid material, characterized in that: The nanocomposite particles composed of disc-shaped anisotropic amino-modified MOF and silica nanoparticles coated thereon are used as the dispersed phase, and dimethyl silicone oil is the continuous phase; the electrorheological fluid dispersed phase first uses a hydrothermal method to prepare disc-shaped NH2-MOF nanoparticles, and then uses a hydrolysis method to coat silica thereon, and finally prepares anisotropic NH2-MOF@SiO2 core-shell nanocomposite materials; the anisotropic NH2-MOF@SiO2 nanocomposite material combines the dual advantages of anisotropy and core-shell type, and has multiple advantages such as small size of nanoparticles. The introduction of polar groups increases the asymmetry of the crystal structure to improve the polarization ability, and the chemically stable and highly insulating silica is coated on the amino-modified MOF to adjust the conductivity. When the voltage is set to 3 kV, a specific shear rate value of 0.1s is selected. -1 The electrorheological efficiency of the obtained sample is 579; at 3000 volts, its shear stress platform area is also close to 360Pa; in short, this comprehensive improvement significantly enhances the overall performance of the material, especially in terms of electrorheological performance.

2. The NH2-MOF@SiO2 core-shell nanocomposite material according to claim 1, characterized in that The preparation process comprises the following steps: (1) 65 mL of N,N-dimethylformamide and 10 mL of anhydrous methanol were added to a beaker in sequence, stirred evenly, and then 2.8 g of aminoterephthalic acid and 0.7 g of terephthalic acid were weighed and added to the solution. Then 0.7 g of hexadecyltrimethylammonium bromide was weighed and slowly added to the prepared mixed solution. The mixture was stirred at room temperature until all the solution was observed to be dissolved. (2) 3.5 ml of acetic acid was slowly injected into the above solution, followed by thorough stirring for 10 minutes; then, 2 ml of tetrabutyl titanate was added dropwise to the continuously stirred mixture, and stirring was continued for 20 minutes. After thorough mixing, the mixture was transferred to a reactor and the temperature was set at 150 degrees Celsius for a 24-hour hydrothermal reaction process; (3) The suspension generated after the reaction was first washed once with dimethylformamide at a speed of 7500 r / min, then washed twice with anhydrous methanol and three times with anhydrous ethanol to remove internal impurities, and the product was dried at 75° C. for 10 hours; (4) Measure 150 mL of anhydrous ethanol and put it into a 200 mL beaker for standby use, weigh 0.5 g of NH2-MOF nanoparticles, dissolve it in it, and stir for 20 minutes; measure and mix 1.2 mL of deionized water and 1 mL of ammonia water to form a mixed solution, and stir for 15 minutes; then add 2 mL of ethyl silicate and stir for 4 hours to form a suspension; after the hydrolysis reaction, the suspension is washed by centrifugation three times with anhydrous ethanol, transferred to a drying oven, and dried at 75°C for 12 hours to obtain a solid powder; (5) The obtained solid powder and dimethyl silicone oil are prepared into an electrorheological fluid at a weight ratio of 10 wt %.